Comparison of Local Anaesthetic Efficacy of Tramadol Versus Lignocaine for Extraction of Tooth Under Supraperiosteal Infiltration - Jendi, Shoeb Kasim (J Maxillofac Oral Surg, 2018)
BACKGROUND: Tramadol has been shown to have a local anaesthetic effect when used as infiltration anaesthesia. METHODS: The local anaesthetic efficacy of tramadol was compared with that of lignocaine for the extraction of teeth in terms of their onset of action, duration of action, intraoperative pain, post-operative analgesic effect and adverse reactions. Apart from this, incidence of allergic reaction was also recorded for both the drugs. A total of 100 patients were divided into two groups randomly. Each patient was assigned to receive either a maximum of 2 ml of 5% tramadol (Supridol 50 mg, Neon laboratories), Group T (n = 50), as a local anaesthetic solution for extraction of maxillary premolar for orthodontic reason under supraperiosteal infiltration following strict aseptic precaution or a maximum of 2 ml of 2% lignocaine (Lox 2%, Neon laboratories), Group L (n = 50), in a double-blinded fashion. RESULTS: In group T, the mean subjective onset of action was 33.66 s, while in group L it was 33.06 s (p = 0.881). In group T, the mean objective onset of action was 3.04 min, while in group L it was 3.18 min (p > 0.05). The mean duration of action in group T was 55.60 min, while in group L it was 57.50 min (p = 0.432). Only 2 patients in group T and 1 patient in group L had nausea (p = 0.245). CONCLUSION: We conclude that 5% tramadol has a local anaesthetic efficacy similar to 2% lignocaine but is comparatively a weaker agent.